Meningkatkan Aktivitas, Keterampilan Komunikasi Dan Hasil Belajar IPS Pada Siswa Sekolah Dasar Menggunakan Model Pemberani - Norlailasari Norlailasari; Raihanah Sari (Jurnal Pendidikan Sosial Dan Konseling, 2024)
The problem in this research is the low level of activity, communication skills and student learning outcomes in social studies content. An effort to overcome this problem is by implementing the BEREBERI model. This research aims to describe educators' activities, improve student activities, communication skills and student learning outcomes. This research uses classroom action research which was carried out in 3 meetings. The subjects of this research were fifth grade students at SDN Murung Raya 3. The results of this research showed thatTeacher activity at meetings 1 to 3 increased and the results were 100% with the criteria "very good". Student activity at meetings 1 to 3 increased and the results were 95% with the criteria "very active". Communication skills at meetings 1 to 3 increased and the results were 89% with the criteria "very skilled". The classical completeness of student learning outcomes at meetings 1 to 3 increased and the result was that 93% of students were "complete". This research can be used as a reference in improving student activities and learning outcomes.